Motivasi Perajin Gula Kelapa Cetak di Desa Pageraji Kecamatan Cilongok Kabupaten Banyumas - Assyahry, Gwynend Dena; Satriani, Ratna; Sunendar, Sunendar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Pageraji Village in Cilongok Sub-district was the center of coconut sugar production in Banyumas Regency. The mould coconut sugar industry in Pageraji Village was facing a decline in the number of penderes due to the high risk of accidents and low income that does not meet the District Minimum Wage (UMK). However, crafters continue to run their businesses due to economic pressure and motivation to fulfill their needs. This study aims to 1) analyze the driving and inhibiting factors of crafters in running a moulded coconut sugar business, and 2) determine the closeness of the relationship between internal and external factors that influence the motivation of crafters in Pageraji Village. The research was conducted using a survey method in Pageraji Village, Cilongok District, Banyumas Regency. The focus of this study was to examine the motivation of moulded coconut sugar crafters in Pageraji Village. Respondents were selected through simple random sampling, resulting in a sample of 119 individuals. The data were analyzed using instrument testing, descriptive analysis, likert scale, and spearman rank correlation analysis. The results show that income, market security, and business continuity are the main motivating factors for moulded coconut sugar crafters in Pageraji Village running their businesses. There are no inhibiting factors that are considered to hinder the moulded coconut sugar business activities, only the risk factor of the crafters when extracting sap and the attachment of the crafters to middlemen, which are considered neutral as inhibiting factors. Family dependents and market security have the strongest correlation with the motivation of moulded coconut sugar crafters in Pageraji Village (correlation coefficient of 0.98), followed by age and risk (0.76), and income and business continuity (0.52).